Pengaruh Rasio Keuangan Terhadap Return On Investment Perusahaan Di Bursa Efek Indonesia - Nurhasanah; Darul Amri; Indra Satriawan; Firmansyah; M.Thoyib; Ari Densyah Ramadhan (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
The writing of this final report proposal aims to determine the factors that affect the return on investment in companies listed on the Indonesia Stock Exchange. The data used in this study is the financial statements of companies listed on the Indonesia Stock Exchange in the consumer goods industry sector. The sample used was 80 samples consisting of cross section data in the form of 20 companies and time series data for 4 years of financial statements starting from 2018 to 2021. This type of research used quantitative research. Data collection techniques using documentation studies. The analysis used is multiple linear regression analysis, t test, f test and R2 test using the SPSS application. The results of the t test show that the current ratio has no positive and significant effect with a significant value of 0.648, which is greater than 0.05. The Debt To Asset Ratio has a negative and significant effect with a significance value of 0.001 less than 0.05. Total Asset Turnover has a positive and significant effect with a significant level of 0.012 which is smaller than 0.05. The results of the F test analysis show a significant value of 0.000 which is smaller than 0.05, thus indicating that there is an influence between Current Ratio, Debt To Total Assets, Total Asset Turnover on Return On Investment simultaneously. The results of the R2 analysis showed a value of 0.243 or 24.3%.